Efektivitas Media Pembelajaran Digital Berbasis Self-Directed Learning Terhadap Pedagogical Content Knowledge Mahasiswa PGSD pada Materi Periodisasi Kesenian Anak - Gozin Najah Rusyada (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the effectiveness of digital learning media based on self-directed learning on the pedagogical content knowledge (PCK) of PGSD students regarding the topic of children's art periodization. The study uses a quantitative approach with a quasi-experimental method through a one-group pretest-posttest design. The research was conducted on second-semester students in class A of the S-1 PGSD Study Program at FKIP Universitas Mataram in the 2025/2026 academic year, with a total of 30 students selected using a saturated sampling technique. Data was collected using a PCK test, observation sheets of student activities, and student response questionnaires. The validity of the instruments was tested through expert judgment, while the reliability of the instruments was analyzed using Cronbach’s Alpha coefficient with a value of 0.872. Data analysis was conducted using descriptive and inferential statistics through the Kolmogorov–Smirnov normality test and paired sample t-test. The results showed that the average pretest score of 61.27 increased to 82.13 in the posttest. The results of the paired sample t-test showed a significance value of 0.000 (<0.05), indicating a significant difference between the pretest and posttest scores. Observations and student survey responses also showed ratings from good to very good regarding the use of digital learning media. The findings suggest that self-directed learning-based digital learning media are effective in improving PGSD students' pedagogical content knowledge on the topic of children's art periodization.